Effects of Oral Administration of Monosodium Glutamate (MSG) on Obesity in Male Wistar Rats (Rattus Norvegicus) - Mulyati Sri Rahayu; Sri Wahyuni; Yuziani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Monosodium glutamate (MSG) is one of the most widely employed food enhancers. Although the umami compound, controversy persists regarding the effects of MSG intake on body weight. Chronic MSG intake may result in excessive body weight gain and obesity. Consumption of MSG result in organ damage, cardiovascular disease, oxidative stress, and also risk factors for obesity. This study aims to determine the effect of oral MSG on obesity in adult male Wistar rats (Rattus norvegicus).Methods: This true experimental study used the post-test control group design. Twenty-four adult male Wistar rats were randomly divided into four groups: control (received distilled water), Group 1 (MSG 0.378 mg/gr BW), Group 2 (0.756 mg/gr BW) and Group 3 (1.512 mg/gr BW). The obesity parameter was obtained by the Lee index. Kruskal-Wallis test follows by Mann-Whitney test were used to compare the Lee index between groups.Results: Lee’s index mean for each group was 358.4%, 314.1%, 287.8%, and 320.9%, respectively. The Kruskal Wallis test showed a significant difference in the Lee index between groups (p = 0.043). A follow-up test using Mann-Whitney found a significant difference between group 2 and the control group (p = 0.043, p <0.05). The mean of Lee index of group 2 was 70.51% lower than the control group.Conclusion: This study concluded that Lee index was not increased in MSG-treated rats than in the control group after oral MSG intervention for 21 days.